Concept of Plyometric Training and Its Effect on Physiological Parameters of Football Players - Laishram Santosh Singh; W. James Singh; Kaukab Azeem; Ningthoujam Meiraba Meitei; Dessalegn Wase Mola (OVS LLC, 2024)
Background. Plyometric training, which consists of exercises that involve rapid and repetitive muscle stretching and contraction, has become increasingly popular for its potential in sports conditioning. Objectives. The primary objective of this study was to examine the principles of plyometric training and to assess how it influences the physiological parameters of football players. Materials and methods. This study involved 30 male football players aged 18 to 24, actively engaged in national-level competition. The participants were randomly divided into two groups: the experimental group (n = 15) and the control group (n = 15), with 15 players in each group. The selected physiological parameters for assessment included aerobic capacity, blood pressure, and pulse rate. Aerobic capacity was measured using Cooper's 12-minute run/walk test, blood pressure was assessed with a sphygmomanometer, and pulse rate was measured using the radial artery method. The six-week plyometric training program, conducted five days a week, involved 60-minute sessions. The experimental group underwent the plyometric training program, while the control group did not engage in any specific exercises. Pre- and post-test scores were analyzed statistically using descriptive statistics and analysis of covariance (ANCOVA). The significance level was set at a confidence level of 0.05. Results. The findings indicate a notable enhancement in physiological parameters among participants in the experimental group as opposed to the control group. The implementation of the plyometric training program proved to be effective in elevating the aerobic capacity, blood pressure, and pulse rate of the football players. Conclusions. The study concludes that a six-week plyometric training program significantly enhances the physiological parameters of football players, including aerobic capacity, blood pressure, and pulse rate. Further research should be conducted to examine the long-term effects and optimal duration of plyometric training, as well as the underlying physiological mechanisms, in order to gain a deeper understanding of its effectiveness and applications in sports conditioning.